The Gamification Effect On Student Achievement, Intrinsic Motivation, Engagement, And Their Relations With Computational Thinking In A Scratch Programming Environment - Rakyan H., Alharbi Khalid (2023)
The current study investigated the effects of gamification elements such as badges, points, and leaderboards on student achievement, intrinsic motivation, and engagement in a scratch programming environment and its relationship with computational thinking.